An Analysis of Grammatical Errors in Writing Made by English Education Students at IAIN Palopo - Faisal Amir; Abidin Pammu; Nasmilah Nasmilah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Considering the importance of grammatical knowledge in the writing process, this research aims at describing the grammatical errors that are committed by the fifth semester students of English Department at IAIN Palopo. The research study is classified into a descriptive-qualitative study. The data were collected from twenty two English texts written by the English Department students which were done as tasks and contained six familiar topics. Students were supposed to write an essay/paragraph about the given topics. In addition, the researcher had permission from the lecturer to take and analyse the students’ written works.  The researcher and students’ written works are the main sources of data collection in this research. To identify the common errors, students’ writings were analysed with the help of checklists in order to classify different types of errors made by the respondents. The results of the study revealed that the most common and frequent errors made by the students are 387 (58.37%) places of omission errors, 213 (32.12%) places of mis formation errors, 131 (19.75%) places of addition errors, 8 (1.20%) places of mis ordering errors. Besides that, the causes of these errors were developmental found in 323 (36.17%) places, 306 (34.26%) of ambiguous, 205 (22.95%) of interlingual, and 59 (6.60%) unique errors. Based on these findings, teachers are suggested to raise students’ awareness on these errors and provide sufficient remedies to prevent students from internalizing such errors.